Building Viksit Bharat: The Human Rights Agenda for 2047 - Jameel, Anas (Society & Sustainability, 2025)
As India approaches its centennial year of independence in 2047, the vision of Viksit Bharat—a developed, inclusive, and equitable nation—requires a paradigm shift in developmental priorities, with human rights as the cornerstone. This paper examines how a rights-based approach can effectively address systemic inequalities and foster sustainable growth, emphasizing the interplay between human rights and critical developmental domains such as education, healthcare, economic equity, and gender justice. The paper’s primary objective is to analyze the current state of human rights in India while identifying actionable strategies to integrate these rights into policy frameworks and governance structures. By bridging the domains of human rights and development, the study provides a comprehensive blueprint for achieving Viksit Bharat 2047. Unlike existing works that address these aspects in isolation, this paper adopts a holistic perspective, linking constitutional principles, global frameworks, and scholarly insights to argue that human rights are both a means and an end to development. The findings underscore the importance of participatory governance, institutional accountability, and inclusive policy-making in realizing a just and equitable society. This study contributes to academic and policy discourse by offering practical recommendations for aligning India’s developmental aspirations with its commitment to human rights. By placing human rights at the center of development, the paper envisions a future where equity, dignity, and justice become lived realities for all citizens of India.